2019
DOI: 10.1038/s41420-019-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominant role of splenic marginal zone lipid rafts in the classical complement pathway against S. pneumoniae

Abstract: Lipid rafts (LRs) play crucial roles in complex physiological processes, modulating innate and acquired immune responses to pathogens. The transmembrane C-type lectins human dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) and its mouse homolog SIGN-R1 are distributed in LRs and expressed on splenic marginal zone (MZ) macrophages. The DC-SIGN-C1q or SIGN-R1-C1q complex could mediate the immunoglobulin (Ig)-independent classical complement pathway against Streptococcus pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…60 DC-SIGN + macrophages are noted as a part of mechanism for Streptococcus pneumonia eradication by complement activation. 61 As the involvement of spleen-derived IgM + memory cells in the immune response against Streptococcus pneumonia is already demonstrated, 47 it could be concluded that interplay of MZB cells and splenic macrophages in humans modulate immune response towards encapsulated pathogens. BCR specificity of MZB cells towards the microbial pattern antigens, such are those found in S pneumoniae, N meningitidis, and H influenza further explain why is immune response to encapsulated bacteria reduced in infant under 2 years of age when splenic MZB cells are not developed yet, or in splenectomized patients.…”
Section: Infectionsmentioning
confidence: 99%
“…60 DC-SIGN + macrophages are noted as a part of mechanism for Streptococcus pneumonia eradication by complement activation. 61 As the involvement of spleen-derived IgM + memory cells in the immune response against Streptococcus pneumonia is already demonstrated, 47 it could be concluded that interplay of MZB cells and splenic macrophages in humans modulate immune response towards encapsulated pathogens. BCR specificity of MZB cells towards the microbial pattern antigens, such are those found in S pneumoniae, N meningitidis, and H influenza further explain why is immune response to encapsulated bacteria reduced in infant under 2 years of age when splenic MZB cells are not developed yet, or in splenectomized patients.…”
Section: Infectionsmentioning
confidence: 99%
“…Depletion of lipid rafts by MβCD treatment resulted in loss of SYK phosphorylation in dendritic cells, supporting a role for lipid rafts in dectin-1 signaling ( 39 ). During Streptococcus pneumoniae infection, splenic marginal zone (MZ) macrophage lipid rafts accelerate pathogen uptake and degradation ( 40 ), as well as mediate DC-SIGN- or SIGN-R1-induced classical complement pathway activation against S. pneumoniae , thereby facilitating rapid clearance of this pathogen.…”
Section: Lipid Raft Involvement In Pathogen Recognition Receptor Signaling and Cytokine Secretionmentioning
confidence: 99%